Interplay of MLCT and ILCT states in rhenium(I) complexes - Gordon, Keith (2020)
Metal complexes with ligands that have charge-transfer electronic structure can lead to interesting interplay between metal-to-ligand and intra-ligand charge transfer excited states (MLCT and ILCT respectively). In a systematic study of [ReCl(CO)3(dppz-(linker)-TPA)] complexes (Figure 1), we find a long-lived excited state that is 3ILCT in nature. This is characterized through transient absorption and emission, transient resonance Raman (TR2), time-resolved infrared (TRIR) spectroscopy and TDDFT calculations. Modulation of the donor and acceptor energies results in changes of the 3ILCT lifetime by one order of magnitude, ranging from 6.1 (± 1) μs when a diphenylamine donor is used to 0.6 (± 0.2) μs when a triazole linker and triphenylamine donor is used. The excited state lifetime may be rationalized by consideration of the driving force within the framework of Marcus theory, and appears insensitive to the nature of the linker. [1,2] However we show in studies of ILCT systems with 1,10-phanthroline ligands the interactions between the MLCT and ILCT states is stronger leading to unpredictable behaviour. For example simple donor tuning using electron withdrawing and donating groups results in emission spectra that appear unchanged with substituent yet actually arise from different states.[3]